2022
DOI: 10.3389/fncir.2022.976789
|View full text |Cite
|
Sign up to set email alerts
|

Convergent and divergent neural circuit architectures that support acoustic communication

Abstract: Vocal communication is used across extant vertebrates, is evolutionarily ancient, and been maintained, in many lineages. Here I review the neural circuit architectures that support intraspecific acoustic signaling in representative anuran, mammalian and avian species as well as two invertebrates, fruit flies and Hawaiian crickets. I focus on hindbrain motor control motifs and their ties to respiratory circuits, expression of receptors for gonadal steroids in motor, sensory, and limbic neurons as well as diverg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 147 publications
0
7
0
Order By: Relevance
“…In comparison to birds, mammals and anurans likely share the neural network architecture of vocal circuits due to their developmental and evolutionary origin (recently reviewed by Barkan & Zornik, 2020; Kelley, 2022). Our results suggest that the archeobatrachian species B. orientalis is an excellent model organism to study the basics of vocal pattern generation in tetrapods.…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…In comparison to birds, mammals and anurans likely share the neural network architecture of vocal circuits due to their developmental and evolutionary origin (recently reviewed by Barkan & Zornik, 2020; Kelley, 2022). Our results suggest that the archeobatrachian species B. orientalis is an excellent model organism to study the basics of vocal pattern generation in tetrapods.…”
Section: Discussionmentioning
confidence: 99%
“…We hypothesize that these differences in the duration of activations should be shown also in an isolated brain preparation of B. orientalis , which has proven to have many advantages for neurobiological research (e.g., Barkan et al., 2017; Leininger & Kelley, 2015; Luksch & Walkowiak, 1998; Luksch et al., 1996). Fictive vocalizations in frogs are known to be elicited and triggered by stimulation of ventral forebrain areas (VFA) such as the extended amygdala as well as the preoptic area (Knorr, 1976; Schmidt, 1973; Brahic & Kelley 2003; Ballagh, 2014; Hall et al., 2013; Kelley, 2022; Kelley et al., 2020). Additionally, fictive vocalizations can be reliably elicited after stimulation of the statoacoustic nerve (N. VIII; Fig.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, Schmidt discovered local field potential activity from the PBN accompanying fictive advertisement calling in the leopard frog, Rana pipiens (Schmidt, 1992), suggesting the conserved role of the PBN in generating vocalizations via exhalation of air in terrestrial species. Considering that the family Ranidae , which includes R. pipiens , diverged from the family Pipidae – which includes the Xenopus genus - ~ 205 million years ago (Roelants et al, 2007) and that amphibians diverged from the Amniota ~ 340 million years ago (Pardo et al, 2017), it is most parsimonious to assume that the involvement of the PBN in vocal production is an ancestral trait in Xenopus (Kelley, 2022). Interestingly, Schmidt observed that the bilateral transection between the PBN and the NA eliminated fictive advertisement calling but that fictive pulmonary respiration persisted in the caudal brainstem of R. pipiens .…”
Section: Discussionmentioning
confidence: 99%
“…The neural basis of primate vocal production has been hotly debated for many years. One recent model 114 states a division into two separate networks (Figure 3), distinguishing between the primary vocal motor network (PVMN), which exists across species, 149 and the volitional articulatory motor network (VAMN). The hypothesis suggests that the VAMN only exists in primate species 114 .…”
Section: Brain Network Underlying Vocal Productionmentioning
confidence: 99%